The Role Of Lng Regasification In Reducing Fuel Consumption And Improving The Reliability Of The Tarakan Isolated System: A Monte Carlo Simulation Approach - Ghusaebi Ghusaebi; Tri Wahyu Adi (Eduvest - Journal of Universal Studies, 2026)
The Tarakan Electricity System is an isolated electricity system that relies on local power plants and local primary energy supply. Reliance on oil-fired (BBM) plants poses challenges to operational efficiency, while gas supply fluctuations, peak load variations, and plant readiness affect system power adequacy. This study aims to evaluate the role of Liquefied Natural Gas (LNG) regasification in reducing fuel consumption and improving the reliability of the Tarakan Electricity System. The Monte Carlo simulation approach is used because average-based deterministic analysis has not been able to represent operational variability, extreme conditions, and power deficit risk in isolated systems affected by uncertainty of gas supply, peak load, and plant readiness. This study uses Monte Carlo simulations based on actual operational data by comparing two scenarios, namely the baseline scenario without LNG regasification and the intervention scenario with LNG regasification. Stochastic input variables include pipeline gas supply, peak load, PLTD readiness, and PLTMG readiness. The input distribution is based on historical data, while the scenario comparison is carried out using the Common Random Numbers (CRN) principle so that the impact of LNG interventions can be evaluated more objectively. The simulation was carried out as many as 10,000 iterations. Fuel consumption models and power models are able to be validated before being used in scenario analysis.